PREDICTING OF DISTRIBUTION CRITICALLY FRACTURE BASED ON STRAIN ANALYSIS AND GEOMECHANICAL APPROXIMATION ON BASEMENT RESERVOIR FOR SIPL FIELD, NORTH EAST JAVA BASIN - Dasa Marianto, Farid
The North East Java Basin has proven hydrocarbon reserves in every reservoir rock layer since the Pre-Tertiary era, evident in oil and gas fields targeting the carbonate rock layer of the Kujung Formation and the clastic sandstone of the Ngimbang Formation. However, exploration activities focusing on the basement rock interval remain limited. This study aims to provide a comprehensive analysis of basement rock fractures through the integration of seismic attribute analysis and strain analysis. The goal is to build a model of basement rock fractures as a reference for exploring the potential reservoirs in the fractured basement rock of the SIPL field. Fracture modeling involves integrating geological data, well log data, seismic data, and final drilling reports from four wells penetrating the basement rock. Seismic attribute analysis, particularly the interpretation of Kmax curvature and Kmax curvature ant track, serves as a reference for defining the orientation of fault and fracture continuity. The results indicate a Northeast-Southwest (NE-SW) strike direction. Additionally, fracture prediction modeling utilizes kinematic approaches and Displacement Discontinuity Method (DDM) as a strain analysis basis for predicting fracture orientations formed concurrently with the main faulting processes. Interpretation of log image data reveals that the orientation of the maximum stress regime is NNE-SSW, indicating the presence of open fractures consistent with the orientation of the global stress map. Geomechanical analysis of the four wells shows the presence of both normal stress regime (Sv > SHmax > Shmin) and shear stress regime (SHmax > Sv > Shmin). This geomechanical analysis is then applied as a basis for predicting fracture orientations conducive to fluid flow. Fracture characterization parameters in this study include dilation tendency. A higher dilation tendency value indicates a more critically stressed fracture. Areas with a population of fractures exhibiting high critical stress become the most permeable zones in the basement rock interval.The North East Java Basin is a proven hydrocarbon-bearing region across every reservoir layer since the PreTertiary era, as evidenced by the presence of oil and gas fields that primarily target the carbonate rock layers of the Kujung Formation. However, exploration activities focused on the underlying basement rock layers remain limited, and within the North East Java Basin, there are no oil and gas fields currently producing from the basement rock layer.